ChemInform Abstract: Efficient Direct 2, 2, 2‐Trifluoroethylation of Indoles via C—H Functionalization. Issue 29 (July 2015) - Tolnai, Gergely L.; Szekely, Anna; Mako, Zita; Gati, Tamas; Daru, Janos; Bihari, Tamas; Stirling, Andras; Novak, Zoltan
Abstract If 3‐methylindole is used as starting material, formation of any trifluoroethylated product is not observed.